Molecular Detection Assays for Rapid Field-Detection of Rice Sheath Blight - Lin, Ying-Hong; Shen, Shih-Mao; Wen, Chen-Jie; Lin, Yi-Jia; Chang, Tsai-De; Chu, Sheng-Chi (Frontiers in Plant Science, 2021)
Rhizoctonia solani (Rs), a soil-borne fungal pathogen, can result in rice sheath blight (ShB), which causes yield loss. To prevent outbreaks of ShB and enhance the sustainability of rice production, it is critical to develop a rapid ShB detection method for specific, fast, and on-site disease management. In this study, a reagent for the rapid extraction of this pathogen was developed for on-site detection. The specificity and sensitivity of a novel SMS RS1-F/SMS RS1-R primer set and a ITS1/GMRS-3 reference primer set were tested, while four different extraction protocols for ShB were developed. Moreover, intraday and interday assays were performed to evaluate the reproducibility of the detection methods developed. The results indicated that all of the developed protocols are suitable for use in detecting ShB. In addition, all the samples of infected rice yielded positive Rs detection results when subjected to TaqMan probe-based real-time PCR and SYBR green-based real-time PCR (SMS RS1-F/SMS RS1-R) tests in which automatic magnetic bead-based DNA extraction was performed. These results indicated that the two molecular detection protocols were suitable for the field diagnosis of ShB for all asymptomatic and symptomatic rice samples.